2006
DOI: 10.1079/bjn20051491
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance threonine requirement and efficiency of its use for accretion of whole-body threonine and protein in Atlantic salmon (Salmo salar L.) fry

Abstract: Eighteen groups of seventy Atlantic salmon (Salmo salar L.) fry (initial mean body weight 0·8 (SD 0·01) g) were fed on semi-purified diets containing graded levels of L-threonine (Thr) in 15 litres aquaria at a temperature of 14·5^18C. Doses of Thr represented 1, 31, 41, 51, 62, 72, 83 and 93 % of its ideal level for optimum protein deposition. Indispensable amino acids other than Thr were included in the same proportion (on a g/16 g N basis) as in the Atlantic salmon fry whole-body carcass. Following 36 d of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 83 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…The reduction in weight gain with arginine levels above the requirement level might be due to (1) extra energy expenditure for deamination; (2) disturbance of absorption and utilisation of other amino acids; (3) lower palatability of the diet; or (4) toxic effects and stress ( 81 ) . A reduction of FI was regarded as the primary factor responsible for the depressed growth observed in Atlantic salmon fry ( 82 ) and European sea bass ( 83 ) . The arginine requirement estimated from SGR by using a quadratic regression analysis was 18·0 g/kg diet, which corresponded to 55·0 g/kg of dietary protein (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in weight gain with arginine levels above the requirement level might be due to (1) extra energy expenditure for deamination; (2) disturbance of absorption and utilisation of other amino acids; (3) lower palatability of the diet; or (4) toxic effects and stress ( 81 ) . A reduction of FI was regarded as the primary factor responsible for the depressed growth observed in Atlantic salmon fry ( 82 ) and European sea bass ( 83 ) . The arginine requirement estimated from SGR by using a quadratic regression analysis was 18·0 g/kg diet, which corresponded to 55·0 g/kg of dietary protein (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Bodin et al (2009) obtained a markedly higher estimate of maintenance lysine requirement (24 mg/kg 0.75 /day) for rainbow trout. Abboudi et al (2006); Rollin et al (2006) estimated the threonine maintenance requirement of Atlantic salmon fry (live weight = 1˗2 g/fish) to be between 5˗7 mg/kg 0.75 /day. NRC (2011) reported that the ideal amino acid patterns are usually stated as the ratio of each EAA to lysine, which is given the arbitrary value of 100.…”
Section: Essential Amino Acid Requirementsmentioning
confidence: 99%